Preparation and Characterization of Self-AssembledManganese Dioxide Thin Films - Pang, S.C.; Chin, S.F.; Ling, Chian Ye (Hindawi Publishing Corporation, 2011)
Thin films of manganese dioxide (MnO2) were prepared by self-assembly of MnO2 nanoparticles directly unto nickel-coated poly(ethylene terephthalate) flexible films using the newly developed horizontal submersion process. The thickness of deposited thin films was controllable by the deposition duration. This horizontal submersion deposition process for thin-film deposition is relatively easy, simple, and cost effective. Effects of deposition duration and calcination temperatures on the microstructure and electrochemical properties of self-assembledMnO2 thin films were investigated. OptimizedMnO2 thin films exhibited high charge capacity, good cycling reversibility, and stability in a mild aqueous electrolyte and are thus promising electrode materials for the fabrication of thin-film electrochemical capacitors.